2017
DOI: 10.12669/pjms.332.11727
|View full text |Cite
|
Sign up to set email alerts
|

The patient safety culture perception of Turkish nurses who work in operating room and intensive care unit

Abstract: Objective:To determine the patient safety culture perception of operating room and intensive care nurses and the factors affecting this perception.Methods:This descriptive study was conducted on 232 nurses working in a Turkish city hospitals. The data obtained from the nurses were collected using personal information form and Patient Safety Culture Scale (PSCS) from June to July 2015.Results:The total score average of the nurses on the PSCS was 2.58±0.39. The nurses obtained the highest score on the employee b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
2
9
3
4
Order By: Relevance
“…Some studies found the malpractice tendency score to be low [12,13,18] while other studies found malpractice tendencies to be high, which mostly resulted from drug and transfusion practices subscales [2,19]. This study found the pediatric nurses' mean PSCS score to be high, which was similar to the findings of other studies [20,21] (Table 2). This situation may result from the in-service training provided to the nurses regarding patient safety.…”
Section: Discussionsupporting
confidence: 84%
“…Some studies found the malpractice tendency score to be low [12,13,18] while other studies found malpractice tendencies to be high, which mostly resulted from drug and transfusion practices subscales [2,19]. This study found the pediatric nurses' mean PSCS score to be high, which was similar to the findings of other studies [20,21] (Table 2). This situation may result from the in-service training provided to the nurses regarding patient safety.…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted in three hospitals in Turkey, which assessed the patient safety culture, observed that having the option to choose the professional unit is a factor that influences the patient safety culture. 28 In contrast, in this study, 76% of respondents stated that they had another employment relationship. The work overload may contribute negatively in the quality of care offered to the patient, favoring the occurrence of adverse events.…”
Section: Discussioncontrasting
confidence: 71%
“…However, in a previous study in an Egyptian ICU, the results within the area/unit comparison revealed that no statistically significant difference exists between the paediatric and adult ICUs for all average scores, except for the nonpunitive response to error (Salem et al, 2019). In comparison with other hospital setting units in a previous study, the PSC score in this study was average in the operating room, whereas the score was at the medium level in the ICU (Rizalar & Topcu, 2017).…”
Section: Discussioncontrasting
confidence: 61%